Mixed methods research - Watkins, Daphne; Gioia, Deborah (Pocket guides to social work research methods, 2015)
"Finally, a practical guide to mixed methods research has been written with health and human services professionals in mind. Watkins and Gioia review the fundamentals of mixed methods research designs and the general suppositions of mixed methods procedures, look critically at mixed method studies and models that have already been employed in social work, and reflect on the contributions of this work to the field. But what is most important is that they lead the reader through considerations for the application of the mixed methods research in social work settings. The chapters of this book are structured so that readers can (figuratively) walk through the mixed methods research process using nine steps. Chapters one, five, and six provide supplemental material meant to serve as grounding for chapters two, three, and four, which outline nine steps in the mixed methods research process, and specific to social work research. This is a short and practical guide not just for learning about mixed methods research, but also doing it"--Provided by publisher.